Vestibular symptoms as the presenting feature of progressive supranuclear palsy. (April 2018) - Haggstrom, Lucy; Brew, Bruce; Sutton, Ian; Tisch, Stephen
Highlights: PSP encompasses substantial phenotypic variability, creating diagnostic difficulty. More variants of PSP are emerging, offering insight into its natural history. We describe three cases with an unusual, vestibular presentation of PSP. Improved description of PSP variants may facilitate diagnosis and management. Abstract: First described in 1964, progressive supranuclear palsy (PSP) is a chronic, sporadic, progressive neurodegenerative tauopathy. Substantial phenotypic variability inherent in PSP confers difficulty to diagnosis. Although the classic presentation, termed PSP-Richardson's syndrome, has been well described, additional variants of PSP are increasingly emerging. Phenotypes described to date include PSP-parkinsonism, PSP-pure akinesia with gait freezing, PSP-corticobasal syndrome or PSP-progressive non-fluent aphasia. However, there has been scant description of vestibular features in PSP. Herein, we report three similar cases with 'probable PSP' who presented with a poorly defined vestibular syndrome and early falls, highlighting an uncommon and as yet under-recognised, vestibular presentation of PSP. Further description of the natural history of this unusual vestibular presentation of PSP may assist in earlier diagnosis and prevent mismanagement of such patients.